SOSIO KULTUR PEMULUNG DAN PERANNYA DALAM KESEIMBANGAN LINGKUNGAN SEKITAR DENGAN MENGKATEGORISASIKAN BARANG BEKAS - Suhartono Suhartono (Sosio-Didaktika: Social Science Education Journal, 2015)
This study aims to describe the socio-cultural, factors that make up the work ethic, and workflow scavengers in categorizing the thrift as a source of information and support materials for learning. The method used in the study is a survey with a qualitative approach that is supported by quantitative data. Primary data was collected by questionnaire and in-depth interviews, secondary data obtained from documents and documentation Pamulang 2. When the study area from August to November 2012 and continued in the months from January to March 2013.  The results showed that almost all scavengers assess both economically job as scavengers can be used as a primary source of income. Skill and dexterity in scavenging into a large capital gain product mulung more. The process contributes to the way categorization of junk into parts easily understood and utilized by stakeholder. Expected investment process at thrift concept has dimensions of knowledge that can be used as a unique learning model for the community. Categorization of secondhand goods can provide economic value to the scavengers also become media education and media knowledge recycling process to balance the surrounding environment. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1350